IMPACT OF HYPOKALEMIA ON HEPATIC ENCEPHALOPATHY AND ITS EFFECT ON DURATION OF STAY IN HOSPITAL - Mirza Waseem Javed; Ejaz Ahmad; Hassaan Ahmad; Zameer Ahmad Nayyer (Journal of Ayub Medical College Abbottabad, 2024)
Background: Hypokalemia is one of the most important precipitating factors of hepatic encephalopathy causing Hypokalemic Alkalosis which is the leading cause of increased levels of nonionic ammonia in blood that crosses the blood brain barrier with ease and accumulates in the Central Nervous System. Methods: A descriptive study was conducted in the Department of Medicine, PAF Hospital, Islamabad from December 31, 2022, to January 1, 2024.The sample size was calculated using WHO sample size calculator and non-probability sampling technique was used. Calculation of mean and standard deviation for variables like Age, Potassium levels and Length of Hospital Stay was done. Frequencies and percentages were calculated for variables like Hypokalemia, Gender, and Ethnicity. Independent samples t-test was used to compare the means, duration of stay at the hospital for patients with and without hypokalemia, keeping the p-value <0.05 as significant. Results: The mean age of patients was 36.76±9.52 years. Out of the total 179 patients considered, 109 patients were male while 70 were females. Sixty-three patients were found to have hypokalemia. Their mean Potassium level was 3.47±0.37 mEq/L. A significant difference (p=0.230) wasn’t detected in patients presenting with hypokalemia with age greater than and less than 35 years of age whereas, a significant difference (<0.001) was detected in the age group of less than 35 years when mean length of hospital stay was calculated. Conclusion: The mean length of hospital stay was significantly higher amongst patients having hypokalemia, compared to those with no hypokalemia.